PROPHYLACTIC PREOPERATIVE LASER RETINOPEXY DOES NOT REDUCE THE OCCURRENCE OF RHEGMATOGENOUS RETINAL COMPLICATIONS IN MACULAR SURGERY. Issue 9 (September 2018) - Garg, Aakriti; Chang, Jonathan S.; Tosi, Gian Marco; Esposti, Pierluigi; Chen, Royce W.; Horowitz, Jason; Hoang, Quan V.; Schiff, William M.; Barile, Gaetano R.; Chang, Stanley
Abstract : Purpose: Knowledge on the utility of prophylactic 360° laser retinopexy before pars plana vitrectomy in the absence of peripheral retinal pathology is limited. This study compares the occurrence of rhegmatogenous events in the setting of small-gauge pars plana vitrectomy with and without prophylactic preoperative laser. Methods: Our multicenter, retrospective case–control analysis reviewed patients who underwent epiretinal membrane removal or macular hole repair through 23- or 25-gauge pars plana vitrectomy: 205 controls who did not receive prophylactic laser and 176 cases who received preoperative prophylactic laser retinopexy anterior to the equator. Main outcome measures were the rate and characteristics of postoperative retinal tears and detachments. Patients with previous pars plana vitrectomy or significant retinal disease were excluded. Results: Of those patients with prophylactic laser and those without, there was no significant difference in the number of retinal breaks (1.7% vs. 0.49%, respectively; P = 0.339) or retinal detachments (0% vs. 0.49%, respectively; P = 1.00). Of the lasered group, there was one sclerotomy-related retinal break and two non–sclerotomy-related retinal breaks. Of the nonlasered group, there was one non–sclerotomy-related retinal break and one sclerotomy-related retinal detachment. Conclusion: Preoperative prophylactic peripheral laser retinopexy does not seem to offer an added benefit in the prevention of intraoperative and postoperative rhegmatogenous events. Abstract : Preoperative prophylactic peripheral laser retinopexy in the setting of small-gauge pars plana vitrectomy for macular disease does not seem to offer an added benefit in the prevention of intraoperative and postoperative rhegmatogenous events. Sparing patients this additional procedure may reduce potential morbidity.